Greenland, view of Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. L.A.B.'s Curry Comb Peak - the highest part of this mountain which overlooks the west side of Left Valley. Noticeable is the great erosion towards the summit. Taken from the eastern side of Left Valley. This is No. 9 in pan D.